Effect of Extender and Cooling Rate on the Quality of Frozen Thawed Semen of Bali Bull (Bos Sondaicus) - Anna Farhana; Zaituni Udin; Jaswandi Jaswandi; Riyan Nugroho Aji (Buletin Peternakan, 2018)
The purpose of this study was to observe the effect of extender and cooling rate on the quality of frozen thawed semen of Bali bull (Bos sondaicus). The experiment was conducted at Laboratory of Animal Biotechnology, Faculty of Animal Husbandry, Andalas University. A completely randomized design of factorial 2 x 3, 2 different extenders and 3 cooling rates with 3 bulls as the replicate. Data were analyzed using analysis of variance (ANOVA). The first factors was extender such as tris citrate egg yolk (TCEY) and tris citrate soy milk (TCSM). The second factors was the cooling rate such as: 15ºC/min, 10ºC/min and 5ºC/min. Variables were: motility, viability, abnormality, and membrane integrity. The results of treatment of TCEY extender on the average of motility 42.67±5.17%, viability of 53.78±3.79%, abnormality of 18.89±1.07%, and membrane integrity of 35.44±3.01%. The effect of cooling rate of 10°C /min has the highest semen motility of 44.35±5.28%, viability of 57.17±1.18%, abnormality of 17.84 ± 0.23 % and membrane integrity of 36.83±2.12%. The interaction between extender and cooling rate was founded significant different (P<0.05). Otherwise of extender and cooling rate on post-thawed of motility, viability and membrane integrity, had no difference (P>0.05) on semen abnormality. It can be concluded that tris-citrate egg yolk (TCEY) extender with cooling rate of 10ºC / min were the best semen motility, viability, and membrane integrity of spermatozoa.